2021
DOI: 10.1021/acscatal.1c04248
|View full text |Cite
|
Sign up to set email alerts
|

Scission of Glucosidic Bonds by a Lentinus similis Lytic Polysaccharide Monooxygenases Is Strictly Dependent on H2O2 while the Oxidation of Saccharide Products Depends on O2

Abstract: Lytic polysaccharide monooxygenases (LPMOs) are mononuclear copper enzymes that act in synergy with glycoside hydrolases to saccharify the most abundant polysaccharides in nature. Both O 2 and H 2 O 2 can be cosubstrates for LPMOs. The Lentinus similis LPMO (LsAA9A) has previously been shown to oxidatively cleave oligosaccharides when supplied with ascorbate as a reductant. This study demonstrates that LsAA9A is unable to complete the catalytic cycle and cleave cellulose without H 2 O 2 . Instead, cellooligome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 54 publications
1
38
0
1
Order By: Relevance
“…Both O 2 and H 2 O 2 have been suggested as natural co-substrates (Bissaro et al, 2017; and the LPMO mechanism is being assessed continuously for the involvement of either/both (Bissaro et al, 2020;Hedega ˚rd & Ryde, 2017;Courtade et al, 2020;McEvoy et al, 2021;Brander et al, 2020). The dependence on H 2 O 2 for saccharide cleavage has been established recently specifically for one of the model LPMOs investigated here (Brander, Tokin et al, 2021), and is generally gaining increasing support. The H 2 O 2 -driven mechanism has the advantage that the LPMO active-site metal only needs to be reduced once, while in the O 2 -driven mechanism, it needs to be reduced at every cycle (Bissaro et al, 2017).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Both O 2 and H 2 O 2 have been suggested as natural co-substrates (Bissaro et al, 2017; and the LPMO mechanism is being assessed continuously for the involvement of either/both (Bissaro et al, 2020;Hedega ˚rd & Ryde, 2017;Courtade et al, 2020;McEvoy et al, 2021;Brander et al, 2020). The dependence on H 2 O 2 for saccharide cleavage has been established recently specifically for one of the model LPMOs investigated here (Brander, Tokin et al, 2021), and is generally gaining increasing support. The H 2 O 2 -driven mechanism has the advantage that the LPMO active-site metal only needs to be reduced once, while in the O 2 -driven mechanism, it needs to be reduced at every cycle (Bissaro et al, 2017).…”
mentioning
confidence: 75%
“…In vitro reductants such as ascorbic acid, gallic acid or cysteine are commonly used (Wang et al, 2020). As well as being essential for further reactivity, there are several reports indicating increased polysaccharide affinity on reduction of the active-site metal, suggesting that polysaccharide binding precedes further steps in the mechanism (Kracher et al, 2018;Filandr et al, 2020;Brander, Tokin et al, 2021). Both O 2 and H 2 O 2 have been suggested as natural co-substrates (Bissaro et al, 2017; and the LPMO mechanism is being assessed continuously for the involvement of either/both (Bissaro et al, 2020;Hedega ˚rd & Ryde, 2017;Courtade et al, 2020;McEvoy et al, 2021;Brander et al, 2020).…”
mentioning
confidence: 99%
“…Computational studies on Ls AA9A have also shown that the H 2 O 2 co-substrate does not require proton transfer (and thus double protonation) [ 27 , 33 ]. A new experimental study further highlights that H 2 O 2 is the co-substrate strictly required for Ls AA9A glycosidic bond cleavage activity [ 28 ]. Thus, at least for Ls AA9A there is currently no evidence of His147 double protonation or proton transfer being necessary for the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The black arrow in Figure 1 (pointing to the chloride ion) denotes the position of the oxygen-species binding site. The oxygen species could be provided by either molecular O 2 or H 2 O 2 , although the support for the latter is increasing [ 25 , 26 , 27 , 28 ]. After binding, the oxygen species is positioned appropriately near the substrate by the residues around the active site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation